Isotopically characterised N2O reference materials for use as community standards. (28th April 2022) - Mohn, Joachim; Biasi, Christina; Bodé, Samuel; Boeckx, Pascal; Brewer, Paul J.; Eggleston, Sarah; Geilmann, Heike; Guillevic, Myriam; Kaiser, Jan; Kantnerová, Kristýna; Moossen, Heiko; Müller, Joanna; et al.
Abstract : Rationale: Information on the isotopic composition of nitrous oxide (N2 O) at natural abundance supports the identification of its source and sink processes. In recent years, a number of mass spectrometric and laser spectroscopic techniques have been developed and are increasingly used by the research community. Advances in this active research area, however, critically depend on the availability of suitable N2 O isotope Reference Materials (RMs). Methods: Within the project Metrology for Stable Isotope Reference Standards (SIRS), seven pure N2 O isotope RMs have been developed and their 15 N/ 14 N, 18 O/ 16 O, 17 O/ 16 O ratios and 15 N site preference (SP) have been analysed by specialised laboratories against isotope reference materials. A particular focus was on the 15 N site‐specific isotopic composition, as this measurand is both highly diagnostic for source appointment and challenging to analyse and link to existing scales. Results: The established N2 O isotope RMs offer a wide spread in delta ( δ ) values: δ 15 N: 0 to +104‰, δ 18 O: +39 to +155‰, and δ 15 N SP : −4 to +20‰. Conversion and uncertainty propagation of δ 15 N and δ 18 O to the Air‐N2 and VSMOW scales, respectively, provides robust estimates for δ 15 N(N2 O) and δ 18 O(N2 O), with overall uncertainties of about 0.05‰ and 0.15‰, respectively. For δ 15 N SP, an offset of >1.5‰ compared with earlier calibration approaches was detected, which should be revisited in the future. Conclusions: A set of seven N2 O isotope RMs anchored to the international isotope‐ratio scales was developed that will promote the implementation of the recommended two‐point calibration approach. Particularly, the availability of δ 17 O data for N2 O RMs is expected to improve data quality/correction algorithms with respect to δ 15 N SP and δ 15 N analysis by mass spectrometry. We anticipate that the N2 O isotope RMs will enhance compatibility between laboratories and accelerate research progress in this emerging field.